Corporate Governance Country Assessment : Bulgaria - World Bank (Washington, DC, 2017)
This report assesses Bulgaria's corporate governance policy framework for publicly traded companies. It highlights recent improvements to laws and regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Bulgaria. This report updates the 2002 Corporate Governance ROSC (CG ROSC). As Bulgaria continues its dynamic pace of reforms, all key stakeholders involved in the reforms process may wish to focus on the following four reform priorities: first, the Financial Supervision Commission (FSC) should continue to strictly enforce existing laws and may wish to focus on how the following three groups "comply or explain" with the recently issued national code of corporate governance (NCGC): (i) holding companies, in which governance practices are considered insufficient; (ii) the largest ten issuers that make-up most of the trading and market capitalization; and (iii) principal issuers on the unofficial market that are driving much of the market's growth. Second, the task force that launched the NCGC may wish to eventually review the NCGC to offer more practical guidance on how to implement good practice. Third, the government and regulators may wish to make minor amendments to the legal and regulatory framework. Fourth and finally, the most important factor to improve corporate governance will be to train and thus, over time, build a cadre of qualified, experienced, and professional directors who are empowered to ensure that the "law on the books" translates into actual practice.